2012
DOI: 10.1111/trf.12055
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to assess the hemostatic function of pathogen‐reduced platelets in patients with thrombocytopenia

Abstract: TEG is sensitive to changes in hemostatic function resulting from a single PLT transfusion. MIR and REF provided similar increments in hemostatic function in the immediate posttransfusion period and at 24 hours. A significant difference detected for ΔMA(24hr-1 hr) suggests different PLT clearance mechanisms. The relationship of these variables to clinically meaningful outcomes, for example, bleeding events or transfusion requirements, has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(68 citation statements)
references
References 49 publications
0
68
0
Order By: Relevance
“…In single‐blind crossover studies, in vivo recovery and survival of PRT‐treated PCs were reduced compared with those of untreated control units, as evidenced by reduced corrected count increment . However, the results of a recent pilot study of PLT function in PRT‐treated PLTs isolated from the circulation of patients after transfusion have suggested that these circulating cells may elicit hemostatic responses comparable to those in untreated PLTs . To develop strategies that minimize the negative effects of PRT, it is necessary to determine the mechanisms by which PLTs are damaged.…”
mentioning
confidence: 99%
“…In single‐blind crossover studies, in vivo recovery and survival of PRT‐treated PCs were reduced compared with those of untreated control units, as evidenced by reduced corrected count increment . However, the results of a recent pilot study of PLT function in PRT‐treated PLTs isolated from the circulation of patients after transfusion have suggested that these circulating cells may elicit hemostatic responses comparable to those in untreated PLTs . To develop strategies that minimize the negative effects of PRT, it is necessary to determine the mechanisms by which PLTs are damaged.…”
mentioning
confidence: 99%
“…Its use in hematology-oncology patients with thrombocytopenia is relatively novel, but interest is growing [8,28]. We found that both gamma-irradiated and untreated PCs significantly improved all TEG variables within 1 h of transfusion, indicating that the transfused PLTs were hemostatically active and that TEG was sensitive to the effects of a single PLT transfusion.…”
Section: Discussionmentioning
confidence: 79%
“…Despite the small sample size, it is clear that TEG measurements demonstrated a hemostatic effect due to PLT transfusion in hematology-oncology patients with thrombocytopenia, and MA results were consistent with PLT counts. However, a common criticism of TEG is that it has not been correlated with more clinically relevant outcome measures such as bleeding events [8]. Apelseth et al [18] recently reported that MA measured by TEG correlates with PLT CIs and bleeding, thus reflecting both PLT viability and functionality in hematology-oncology patients and demonstrating TEG's clinical utility in this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations